Termékpálya-fázisok a juhászatban - Cehla, Béla (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
It is not enough to evaluate only natural data in order to carry out an analysis of agricul-tural sectors. If one wants to put together a realistic analysis, the phases of the sector's supply chain should also be considered. The hierarchical relations of each phase point to structural problems and even strengths of the given sector. The production/processing potential of each layer can reveal the short-comings and strengths of production and processing. The quantity of goods in trade, their composition and the balance of goods produced by producers shows the tendencies which all participants of the supply chain have to adapt to. In my current paper, I examined all phases of the sheep supply chain in order to pin-point the problems whose solution is essential for the existence of the Hungarian sheep farming.